WHY DO PEOPLE TRANSACT ON MOBILE INSTANT MESSAGING C2C COMMUNITIES? A CONSUMPTION VALUES THEORETICAL EXPLANATION - Marumbwa , John; Makumbe , William (Electronic Journal of Business and Management, 2021)
With the rise of the fourth industrial revolution and social commerce, Mobile Instant Messaging (MIM) mediated Consumer-to-Consumer (C2C) online communities have flourished. Despite their growth, the motivations for transacting in these novel communities remain underexplored. This study adopts the Consumption Values Theory (CVT) to analyze the drivers behind consumers’ intentions to transact. A theoretical model was empirically tested using data from 250 C2C community members. The findings confirmed that emotional, social, conditional, and epistemic values are positively associated with the intention to transact. Interestingly, functional value was found to be negatively associated with the intention to transact. These insights assist managers in focusing on specific value-creation strategies that resonate with C2C community members.